Powder injection molding of SS 316L/TiC composite - Rudyani Supati. (2008)
The powder injection molding (PIM) of a new metal matrix composite (MMC) comprising of water-atomized 316L stainless steel powder and 3 wt. % TiC particulate reinforcement was carried out in this research. The main objective of this work was to produce defect-free 316L stainless steel MMC parts and to compare the mechanical properties with unreinforced 316L stainless steel parts. Prior to the sintering step, suitable process conditions for mixing, injection molding and debinding were established. In the mixing study, the experimental materials were characterized, suitable powder loading and mixing parameters were established. The results show that the feedstock mixed in the sigma blade mixer followed by a two-pass extrusion gives the best feedstock homogeneity. The feedstock viscosity was characterized within a permissible range of molding temperatures and was determined to be less than 1000 Pa.s which is suitable for injection molding.